"Supportive” Friends vs. "Toxic” Friends: Aspek-Aspek Pertemanan yang Mendukung dan Menghambat Kesehatan Mental Anak Muda selama Pandemi Covid-19 - Muhiddin, Syurawasti; Dewi, Claudia Rosari; Massinai, Sitti Muthia Maghfirah (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
This research aimed to explore the factors that promote and hinder youth's mental health during the pandemic. A total of 151 participants (79% female) aged 18-30 years completed an online survey included open-ended questions about their friendship experience. Thematic analysis using an inductive approach yielded several themes. Social support, communication, quality time, openness, emotional bonds, empathy, guidance, and advice were identified as relational aspects that promote mental health. Lack of social support, ineffective communication, emotional and physical distance, and conflicts were identified as relational aspects hindering mental health. Toxic relationship tendencies, such as judgment and imposition, were also considered detrimental to mental health. Furthermore, personal aspects such as integrity in friendship were perceived as positive for mental health, while certain negative personality traits, negative feelings, and thoughts were seen as harmful. The way young people define supportive friends versus "toxic" friends can differ across contexts other than pandemic.